THE EFFECTS OF PREHEAT AND FILLER BUFFER LAYER ON THE MATERIALS OF ASTM A36 IN THE HARDFACING OVERLAY WELDING TO THEIR HARDNESS AND METALLOGRAPHY - Mohammad Afif Hamdani; Dika Anggara; Rikat Eka Prastyawan (International Conference on Maritime Technology and Its Application, 2024)
ASTM A36 steel overlay products have been used by the industry as liners to protect the main material from abrasion attacks that will occur. From the background above, the formulation of the problem can be written "How were the effects of variations in preheat and filler metal buffer layers in the hardfacing overlay welding of ASTM A36 materials to the hardness values and metallography?" The purpose of this study was to find the results of each test. The experimental research design was used by giving the preheat variations of 1000 and 2000 and filler buffer layers E308LT and E316LT. The hardfacing overlay welding process was carried out by using special electrodes with high hardness. The results of the hardness test showed the highest value, namely 698.7 HVN on the specimen with the E316LT buffer layer. The macro test results showed the fusion in welding results. On the other hand, the results of micro testing in the hardfacing layer area were dominated by primary carbide and austenite. The conclusion of this study was that the higher the preheat temperature process, the lower the hardness value. The selection of buffer layer electrodes with a small Ni composition increased the hardness value. This study is expected to contribute to the industry working on hardfacing overlay impressions as the reference.